Pemanfaatan Pasir Pulau Bungin Kabupaten Kuantan Singingi Sebagai Agregat Halus Pada Campuran Laston Lapis Antar (AC-BC) - Cici Amelia Hilman; Agus Ika Putra; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Sand of Pulau Bungin is natural sand derived from the Batang Kuantan river, Kuantan Singingi Regency. The existence of natural sand availability makes the progress of the construction of Kuantan Singingi Regency because easily obtained, and more economical no need to bring in sand material from other areas and not have to go through the process of solving stone by stone crusher. Based on the specifications of the Bina Marga 2010, the use of natural sand is to mix asphalt concrete (AC) shall not exceed 15% of the total weight of a mixture of aggregates. Therefore we need to know the efficiency use of natural sand in the mix asphalt concrete (AC) for optimum use. This research aims to find out how the levels of optimum asphalt (KAO) and knowing the characteristics of Marshall does meet the general specifications Bina Marga 2010 Revision 3. The variation of fine aggregate natural sand used in this research is 0%, 5%, 10%, 15% and 20% of the total weight of a mixture of aggregates. The addition of natural sand in asphalt concrete base course (AC-BC) causes the value of the levels of optimum asphalt (OBC) decreased. On the mixture of asphalt concrete base course (AC-BC) the addition on variation 10% of the sand obtained the value of the levels of optimum asphalt (KAO) is 6.20% and the maximum stability value is 1440.19 kg. Without considering the limitations on use of sand nature as set forth in the general specifications of the Bina Marga 2010 Revision 3, the addition of natural sand that still might be used in the asphalt concrete base course (AC-BC) until 20%.Keywords: natural Sand Pulau Bungin, asphalt concrete layer between the (AC-BC), a general specification Bina Marga 2010 Revision 3, characteristics of Marshall.